Mechanism for the Regulation of Cell Division in Agmenellum - Ingram, L. O. (1973)
We describe a nonlethal temperature-conditional mutant of Agmenellum quadruplicatum which allows dissociation of the processes of growth and cell division. With this system, evidence has been obtained for the regulation of one step in the process of cell division by a small effector molecule. The effector molecule is apparently released into the surrounding medium and can be obtained from lyophilized spent medium by extraction with 80% ethanol. The addition of this extract to serpentine filaments of the SN29 mutant strain stimulates cell division in these filaments and leads to the production of cells approximating normal dimensions within one generation time. The degree of stimulation of cell division is directly related to the amount of extract added. A general hypothesis is presented for the positive regulation of the initiation of cell wall and cell membrane invagination in this organism.